Macroeconomic and Demographic Determinants of Residential Property Prices in Malaysia - Trofimov, Ivan D.; Nazaria, Md. Aris; Xuan, Dickson C.D. (Faculty of Economics and Business, University of Zagreb and De Gruyter Open, 2018)
This paper studies the relationship between residential property prices and macroeconom- ic and demographic determinants in Malaysia. In the years following the Asian nancial crisis, property prices in Malaysia rose substantially, resulting in an affordability crisis and ultimately policy responses to the problem. Using unit root, Johansen-Juselius cointe- gration, VECM-based Granger causality tests and variance decomposition, and consider- ing quarterly data that covers 2000-2015 period, we established that residential property price growth is principally driven by strong demographic performance and population growth and is backed by the low interest rate environment and rising consumer prices. Household income and level of GDP do not appear to contribute to property price growth. Certain distortions and asymmetries in the Malaysian real estate markets are documented: oversupply in the higher price segment of the market coupled with the lack of affordable housing in the lower price segment; household income growth lagging behind GDP and property price growth, thereby dampening housing demand; growing rental markets in major urban areas as a result of the affordability crisis; and a quality mismatch between buyers’ preferences and housing supply. Keywords: property prices; housing; cointegration